Comparison of immunoperoxidase staining with indirect immunofluorescence, ELISA, and Western blotting assays for detecting anti-HTLV-I antibodies in systemic lupus erythematosus. Issue 1 (January 1988) - Yamaguchi, K; Matutes, E; Kiyokawa, T; Nishimura, Y; Ishii, T; Takatsuki, K; Catovsky, D
Abstract : Serum antibodies against human T cell leukaemia virus type I (HTLV-I) were investigated in 12 patients by four methods: indirect immunoperoxidase staining, indirect immunofluorescence, enzyme linked immunosorbent assay (ELISA), and strip radioimmunoassay based on the Western blotting assay. Seven patients had systemic lupus erythematosus (SLE) and five various autoimmune diseases with one or more circulating autoantibodies. Serum samples from three patients were found to be HTLV-I-positive by the ELISA assay and sera from five patients showed a non-specific reaction by indirect immunofluorescence. These sera were negative when tested by indirect immunoperoxidase staining and Western blotting assay. All four methods gave positive results when tested with samples from 19 HTLV-I carriers and 16 patients with adult T cell leukaemia. Indirect immunoperoxidase staining and Western blotting assay are probably useful and more specific assays for the detection of anti-HTLV-I antibodies in samples from patients with autoimmune diseases.